Individualized teaching aimed at stimulating the development of talent and creativity in students - Arsić Zvezdan M. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2013)
The time in which we live is characterized by rapid and conflicting changes as well as the development of all segments of social life. Access to the civilization of knowledge whose objectives, processes, and outcomes confirm that the human factor is becoming a leading cause of progress, requires redefinition of the relationship between society and schools. In the process of the cultural development, there is a need for talented and creative members of society who are going to be prepared for the leading roles through the educational system. However, in the teaching process, the gifted and creative students very often face a number of difficulties and problems that interfere with their optimal development. They are primarily victims of ignorance and disregard of individual differences among children of the same age, even children with the same IQ. For this reason, the main focus of this paper is on creating the conditions that can contribute to overcoming the problems that gifted and creative students encounter in the present circumstances of the organization and application of the process. Individualized instruction is a reasonable basis for success in this area, since it allows the contents, organization, methods and means of teaching, and learning adapt to individual differences, needs and abilities of students.